Pure Magnesium Gbr Membrane Affects Oral Tissue Regeneration - Guanxi, Wu; Chuanbin, Guo; Jianmin, Han (International dental journal, 2025)
We applied pure magnesium GBR membrane, which demonstrates degradability and favorable mechanical properties, to animal tooth extraction sockets to investigate its effects on the healing of oral soft and hard tissues, as well as the underlying mechanisms. Eight-week-old male SD rats (LA2022015) were assigned to three groups: pure magnesium, titanium, and sham surgery. GBR membranes made from these materials were implanted beneath the gingiva of anterior tooth extraction sockets, covering the alveolar bone. Changes in mucosa defect area were monitored within 7 days. Micro-CT scans were used to assess bone formation at 28 days post-surgery. Besides, 8-week-old female C57BL/6N mice underwent palatal mucosal incision and implantation of different membrane materials beneath the mucosa. At 7 days post-surgery, palatal mucosa samples were collected for flow cytometry and PCR analysis to evaluate cellular composition and molecular expression. The pure magnesium group exhibited slower soft tissue healing of the socket compared to the other two groups. Micro-CT imaging revealed that the pure magnesium group had a significantly higher alveolar bone height and greater bone tissue volume. Analysis of the palatal mucosa in mice indicated that, 7 days post-surgery, the pure magnesium group showed a higher level of innate immune cell infiltration and elevated expression of pro-inflammatory molecules. Magnesium-based GBR membrane positively influences alveolar bone height preservation and bone healing in tooth extraction sockets. However, during the early stage of implantation, it inhibits soft tissue healing by promoting inflammation.